The interaction between [Pt(µ-Cl)(Safrole-1H)]2 and 1,3-diisopropylbenzimidazolium bromide in the presence of Ag2O - Mai, Nguyen Thi; Thao, Pham Thi Minh; Chi, Nguyen Thi Thanh (Vietnam Journal of Science and Technology, 2020)
The interaction of the dimeric complex [Pt(µ-Cl)(Saf)]2 (1) (Saf: deprotonated safrole) with the salt iPr2-bimy·HBr in the presence of Ag2O in acetone solvent was studied. The obtained products were mixed complexes of [PtCl(Saf)(iPr2-bimy)] (2) and [PtBr(Saf)(iPr2-bimy)] (3) with different molar ratio (PI, PII, PIII) depended on the used molar ratio of 1:salt:Ag2O. In the case of this ratio being 1:2:1.1, the mixture PI with 75% for the complex 2 was obtained. When concentration of the salt was increased, the product was PII with the molar ratio of 2 : 3 of 1 : 3. However, when both the salt and Ag2O were increased at the same time, 2 and 3 in PIII had equal molar proportions. The two main factors affecting the 2 : 3 molar ratio are the different solubility of AgCl and AgBr and the different coordinating ability of Cl- and Br- ligands. The structure of 2 and 3 was determined by 1H NMR spectra and single crystal X-ray diffraction. The results reveal that Saf in 2 and 3 coordinates with Pt(II) via C=Colefinic and C5 of benzene ring. Meanwhile, iPr2-bimy coordinates with Pt(II) through CNCN and is in trans-position compared with the C=Colefinic bond.